(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Currently, SX and SS-15A types of separators are used in production. Separators are used to separate the seeded cotton from the air stream coming through the pneumatic conveying device. Also, the separator cleans the cotton from dust and some small impurities as it transfers the dust and small impurities in the cotton together with the air.